Clinical considerations for the management of psoriasis in women with disorders of the menstrual cycle - Dyulmesova-Bilash, Olga (Journal of Education, Health and Sport, 2021)
Introduction. Psoriasis in women of reproductive age is one of the most pressing medical and social problems. The consequence of psoriasis disease is a significant decrease in the quality of life, disability of patients, difficulties in creating a family and deterioration of family relations, significant psychological discomfort. Objective of the study: to increase the effectiveness of treatment of women with psoriasis with menstrual irregularities by means of pathogenetically substantiated therapy based on the study of hormonal changes. Materials and research methods. The study included 130 women who were divided into three groups: the main group – 75 women with psoriasis with menstrual irregularities, who were randomized into 3 subgroups: 1a – 25 patients who will receive standard psoriasis therapy; 1b – 25 patients, in addition to the standard treatment of psoriasis, will receive gestagens for 3 months; 1c – 25 patients, in addition to the standard treatment of psoriasis, will receive a preparation of an dry extract of herb of creeping anchors for 3 months. The comparison group consisted of 25 women with psoriasis without hormonal disorders, comparable in age and social status with the study group. The control group – 30 apparently healthy women, comparable in age and social status with the study group. Research results. In patients of the main group who received standard psoriasis therapy (1a); who received progestogens for 3 months in addition to standard psoriasis treatment (1b) and, in addition to the standard treatment of psoriasis, who received the preparation of an dry extract of herb of anchors creeping for 3 months (1c), before the start of the treatment, the ratio of LH / FSH – luteinizing hormone (LH) and follicle-stimulating hormone (FSH) was below normal, which indicates a certain deficit in LH production relative to FSH values. In parallel, in these cohorts, the production of prolactin was increased, which suppresses the formation of FSH and LH in the pituitary gland. Changes in the production of gonadotropic hormones are a reaction to the existing deficiency or excess of sex hormones. In the main 1a, 1b and 1c in groups, estradiol values ​​were within the normal range with progesterone deficiency in the luteal phase. The testosterone value in all study groups did not deviate from the standard values. Conclusions. The obtained results of the survey indicate the need to increase the effectiveness of treatment of women with psoriasis with menstrual irregularities by involving measures aimed at correcting hormonal status in complex therapy.